Famotidine induced hypomagnesemia leading to hypocalcemia - Essrani, Rajesh (Oxf Med Case Reports, 2020)
Fifty-five-year-old female with a past medical history of gastroesophageal reflux disease was admitted to hospital due to increased confusion, and muscle cramps for last 15 days. She was taking famotidine 20 mg twice a day for the last 2 years. She was alert and oriented to person and place only. She had dry skin, positive Chvostek’s and Trousseau’s sign. Blood work showed 141 mmol/L of sodium, 0.7 mg/dl of creatinine, 5.7 mg/dl of calcium, 0.55 mg/dl of magnesium, low PTH but normal parathyroid related peptide PTHrP, vitamin D (25) and vitamin D (1.25). She was discharged home on electrolyte supplements. She was readmitted with very low calcium and magnesium. Extensive workup including 24 h of urine calcium and magnesium was unimpressive. She was treated with IV therapy and discharged to follow up with nephrology in the clinic, and famotidine was discontinued on second discharge. Her calcium and magnesium levels remained normal, and in a few weeks later, oral electrolyte supplements were discontinued.